Sinkretisme dalam Agama Hindu dan Buddha di Bali - I Nyoman Kiriana (UHN IGB Sugriwa Denpasar, 2015)
In religious life, at first the existence of Hindu and Buddhist very harmonious and contradictory in their home country, namely India. But the two religions in Indosesia seem very harmonious, especially in the era of the Majapahit kingdom. Moreover, the existence of Hinduism and Buddhism in Bali very harmony and even complement each other in practice and spiritual order. Buddhism is very much a substance similar to the teachings of Hinduism. In some Hindu literature was found a lot in common with the essence of Buddhism, and vice versa. Very often found literature-literature that reflects the harmony of both religions, among others: Lontar Siwagama, Kekawin Mahabharata, Ramayana Kekawin, Kekawin Arjuna Wiwaha, Kekawin Bharata Yudha and Kekawin Sutasoma, Sanghyang Kamahayanikan, Bubugsah Gagakaking and so on. By looking at it as if the two religions fused in practice in Bali, especially in the implementation of religious activities such as the ritual tawur agung in connection with the celebration of Nyepi Saka as the New Year.